Employing Notonagoro Semiotics in Deconstructing Public Sector Organization Performance - Nanda Widaninggar (International Journal of Religious and Cultural Studies, 2022)
This study aims to find the philosophy and concepts in the accounting field related to the public sector organizations based on the Notonagoro’s Hierarchical-Pyramidal of Pancasila which breathes local wisdom and religious universals. This deconstruction is focused on the development of constitutionally public management in Indonesia and relate it into public sector organizational accountability assessments. This article is interdisciplinary in nature, comprising synthesis of Notonagoro's writings, using the Notonagoro’s Hierarchical-Pyramidal Semiotics methodology. This article contributes to a brief synthesis, taken from Notonagoro's writings related to the public management in Indonesia and Pancasila as the basis of state philosophy which is more humanist, emancipatory, transcendental, and teleological. The result is that Notonagoro's Hierarchical-Pyramidal (1) has not been used in public management in Indonesia, (2) can be synthesized as Notonagoro Public Management, (3) public sector organizational accountability assessments should reflect every precept in Pancasila as the basis of nation philosophy.